Low-carbon high-performance cement clinker and preparation method thereof

By replacing some cement raw materials with unground steel slag and adding specific seasoning materials, low-carbon and high-performance cement clinker containing high-active R-type tricalcium silicate is prepared, which solves the utilization and maturation of industrial solid waste resources The problem of low gelling performance of the material has achieved efficient and environmentally friendly cement clinker production.

CN119390364AActive Publication Date: 2025-02-07CHINA BUILDING MATERIALS ACADEMY CO LTD

Patent Information

Application Number
CN202411583303.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-07
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

It is difficult for the prior art to effectively utilize industrial solid waste resources such as steel slag to prepare high-performance low-carb cement clinker, and the crystal form of tricalcium silicate in the clinker is still a low-active M crystal form, with low gelling performance.

Method used

By replacing some cement raw materials with unmilled steel slag, and adding seasoning materials such as lead-zinc slag, copper slag, manganese slag, lithium slag, and high-temperature calcination and quick-cooling treatment, a high-active R-type silicate three are prepared. Calcium low-carbon high-performance cement clinker.

Benefits of technology

The resource utilization of steel slag is realized, the production cost of cement clinker is reduced, the compressive strength and gelling performance of clinker is improved, and it is environmentally friendly, safe and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390364A_ABST
    Figure CN119390364A_ABST
Patent Text Reader

Abstract

The invention relates to a low-carbon high-performance cement clinker and a preparation method thereof. Relates to the technical field of building materials, in particular to a low-carbon cement clinker and a preparation method thereof. The cement clinker comprises the following raw material components in percentage by weight: 75-90% of a raw material, 5-20% of steel slag and 2-8% of a tempering material, and the tempering material comprises at least two of lead-zinc slag, copper slag, manganese slag and lithium slag. The weight percentage of the lead-zinc slag in the tempering material is 0-5.5% according to the oxide ZnO; the weight percentage content of the copper slag is 0-2.0% based on the oxide CuO; the weight percentage of the manganese slag is 0-7.0% in terms of oxide MnO2; and the weight percentage content of the lithium slag is 0-3.0 wt% according to the oxide Li2O. The tempering material is added, the purposes of stabilizing R-type tricalcium silicate and improving the strength of the clinker are achieved by guaranteeing the content of zinc or copper or manganese or lithium in the clinker, components such as fluorine and sulfur which pollute the environment are not additionally added, the clinker is environmentally friendly, safe and reliable, and the used raw materials are wide in source and high in applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a low-carbon cement clinker and a preparation method thereof. Background Art

[0002] The chemical composition of steel slag is similar to that of silicate cement clinker. If the chemical composition of steel slag can be adjusted to meet the requirements of cement clinker, then steel slag can be used as raw material for cement production. This can not only reduce carbon emissions in the cement production process, but also solve the problems of environmental damage and resource waste caused by the long-term accumulation of steel slag.

[0003] The high iron content in steel slag makes it difficult to grind, which affects its economic benefits as cement raw material. If the granular steel slag after iron selection in the steel plant is directly reconstructed at high temperature at the kiln tail, and replaces part of the cement raw material to produce cement clinker, its iron component is conducive to the formation of liquid phase at a lower temperature, which plays a role in promoting melting. The existing silicate phase in the steel slag can also play a role in inducing nucleation of crystal seeds and promoting the formation of clinker. During the sintering process, the larger steel slag particles are broken under the action of sudden heat, which reduces the particle size of the steel slag particles. The surface of some steel slag particles begins to melt, forming more flux minerals, promoting the high-temperature sintering reaction of the raw material, and forming clinker minerals. At the same time, the f-CaO in the steel slag is consumed to form the clinker mineral phase, and the low-activity γ-dicalcium silicate is also reconstructed and converted into high-activity dicalcium silicate. However, in comparison, since the crystal form of the main cementing mineral tricalcium silicate in this clinker is still mainly M crystal form, its cementing performance is still lower than that of traditional clinker.

[0004] A search revealed that Patent ZL201410265848.7 discloses a silicate cement clinker and a method for preparing the same, which introduces ions by adding magnesium-containing raw materials or phosphorus-containing raw materials to the raw materials to achieve the transformation of tricalcium silicate into the R crystal form; however, the patent still uses traditional raw materials to produce clinker and does not play a role in the resource utilization of industrial solid waste.

[0005] Patent CN201510382980.0 discloses a small-particle cement clinker, and patent CN201611145160.0 discloses a cement clinker and a preparation method and application thereof. The above two patents apply industrial waste residues to cement clinker production, but the crystal form of tricalcium silicate in the clinker remains unchanged.

[0006] Therefore, how to make full use of solid waste resources such as steel slag to save natural mineral resources and use solid waste for the preparation of high-performance low-carbon cement clinker has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0007] In view of the above problems, the present invention provides a low-carbon high-performance cement clinker and a preparation method thereof, which effectively utilizes steel slag, and the tricalcium silicate in the prepared clinker is a highly active R crystal type, and the clinker has high strength.

[0008] The technical solution of the present invention is: a low-carbon high-performance cement clinker, wherein the raw materials in the cement clinker include the following components by weight percentage: 75-90% of raw material, 5-20% of steel slag and 2-8% of quenching and tempering material, The tempering material includes at least two of lead-zinc slag, copper slag, manganese slag and lithium slag.

[0009] The lead-zinc slag in the tempering material has a weight percentage of 0-5.5% as ZnO oxide; the copper slag has a weight percentage of 0-2.0% as CuO oxide; the manganese slag has a weight percentage of 0-7.0% as MnO2 oxide; and the lithium slag has a weight percentage of 0-3.0wt% as Li2O oxide.

[0010] The minerals in the cement clinker include tricalcium silicate in a content of 45-70wt% by weight, and its crystal form is R type.

[0011] The limestone saturation coefficient of the cement clinker is in the range of 0.82-0.94%; the silicon content is in the range of 1.7-2.7%; and the aluminum content is in the range of 0.8-1.7%.

[0012] The steel slag is not ground, and the particle size of the steel slag is ≤15mm.

[0013] A method for preparing low-carbon high-performance cement clinker comprises the following steps: Step 1, selecting the type of conditioning material according to the required composition of cement clinker, and determining the weight ratio of each conditioning material component; Step 2: fully mix the raw meal, steel slag and the above-mentioned tempering material, then calcine at high temperature and quickly cool to room temperature to prepare cement clinker.

[0014] The temperature range of high temperature calcination is 1400℃~1500℃.

[0015] Grind the obtained cement clinker to control the sample fineness and grind it to a specific surface area of ​​320~360m 2 / kg.

[0016] In the process of the present invention, steel slag is used to replace a part of cement raw materials to prepare cement clinker, which not only effectively realizes the resource utilization of steel slag, but also reduces the production cost of cement clinker and saves natural mineral resources. It is proposed to add tempering materials to ensure the content of zinc, copper, manganese or lithium in the clinker, so as to achieve the purpose of stabilizing R-type tricalcium silicate and improving the strength of clinker, without adding additional components such as fluorine and sulfur that pollute the environment, so it is environmentally friendly, safe and reliable, and the raw materials used are widely available and have strong applicability. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a schematic diagram of the local characteristic fingerprint area of ​​tricalcium silicate of the clinker sample in Comparative Example 1 of the present invention; Figure 2 Schematic diagram of the local characteristic fingerprint area of ​​tricalcium silicate of the clinker sample in Example 1 of the present invention. DETAILED DESCRIPTION

[0018] The present invention will be further described below in conjunction with specific examples, but the following examples should not be construed as limiting the present invention.

[0019] The present invention replaces part of the cement raw material with steel slag, and simultaneously adds a tempering material containing specific trace elements to temper the steel slag and clinkerize it, so as to form highly active R-crystalline tricalcium silicate, prepare low-carbon and high-performance cement clinker, realize resource utilization of steel slag and improve clinker performance.

[0020] Clinker often contains no or very small amounts of impurity ions, mainly monoclinic M3 crystal type. The present invention introduces a quenching and tempering material into the clinker, which not only realizes steel slag as a raw material for producing cement clinker, but also introduces a certain content of Zn, Cu, Mn and Li into the clinker, and can prepare low-carbon high-performance cement clinker containing highly active R-type tricalcium silicate. The high performance in the present invention is specifically reflected in high compressive strength.

[0021] The low-carbon high-performance cement clinker of the present invention comprises the following components by weight percentage: 75-90% of raw material, 5-20% of steel slag and 2-8% of quenching and tempering material. The tempering material includes at least two of lead-zinc slag, copper slag, manganese slag and lithium slag, and is used to adjust the content of trace components in the clinker.

[0022] The present invention proposes to replace part of cement raw materials with steel slag to produce cement clinker. In order to further improve the strength performance of the cement clinker, it is proposed to add a quenching and tempering material to improve the crystal form of the main minerals of the clinker.

[0023] Steel slag contains trace amounts of impurity ions, which can cause lattice distortion of tricalcium silicate, change the symmetry of the crystal structure, and induce the transformation of the tricalcium silicate crystal form to the highly active R-type, thereby improving the strength of the clinker.

[0024] In the present invention, steel slag is a minor component, and the impurity ions introduced by it are relatively small, which are insufficient to cause the crystal transformation of tricalcium silicate. Therefore, the amount of these ions is supplemented by adding a quenching and tempering material, and the "induction" of steel slag is combined to achieve the purpose of optimizing the crystal form of tricalcium silicate.

[0025] The lead-zinc slag in the tempering material has a weight percentage of 0-5.5% as ZnO oxide; the copper slag has a weight percentage of 0-2.0% as CuO oxide; the manganese slag has a weight percentage of 0-7.0% as MnO2 oxide; and the lithium slag has a weight percentage of 0-3.0wt% as Li2O oxide.

[0026] The minerals in the cement clinker include tricalcium silicate in a content of 45-70wt% by weight, and its crystal form is R type.

[0027] The limestone saturation coefficient (KH) of the cement clinker is in the range of 0.82-0.94%; the silicon content (SM) is in the range of 1.7-2.7%; and the aluminum content (IM) is in the range of 0.8-1.7%.

[0028] The steel slag is not ground, and the particle size of the steel slag is ≤15mm. No grinding is required, and the production energy consumption is not increased.

[0029] A method for preparing low-carbon high-performance cement clinker, The following steps are involved: Step 1, selecting the type of conditioning material according to the required composition of cement clinker, and determining the weight ratio of each conditioning material component; Step 2: fully mix the raw meal, steel slag and the above-mentioned tempering material, then calcine at high temperature and quickly cool to room temperature to prepare cement clinker.

[0030] The low-carbon high-performance cement clinker prepared by the present invention contains trace zinc, trace copper, trace manganese, trace lithium, and 45% to 70% of R-type tricalcium silicate.

[0031] The synergistic effect of elements such as Zn, Cu, Mn and Li can cause lattice distortion of tricalcium silicate, change the symmetry of the crystal structure, and induce the transformation of the tricalcium silicate crystal form to the highly active R-type, thereby improving the strength of the clinker.

[0032] The temperature range of high temperature calcination is 1400℃~1500℃.

[0033] Grind the obtained cement clinker to control the sample fineness and grind it to a specific surface area of ​​320~360m 2 / kg.

[0034] The cement clinker prepared by the invention has high strength. When preparing cement with the same strength grade, the amount of clinker can be reduced, the amount of admixture can be increased, the application efficiency of the clinker can be improved, and energy can be saved, waste can be utilized and emission can be reduced.

[0035] The tricalcium silicate in the cement clinker prepared by the present invention is of R type, and the compressive strength of the clinker can be greatly improved compared with the clinker not implementing the present technology.

[0036] The present invention replaces part of the cement raw material with steel slag, and simultaneously adds a tempering material containing specific trace elements to temper the steel slag and clinkerize it, and allows tricalcium silicate to retain the highly active R crystal form to prepare low-carbon and high-performance cement clinker, thereby realizing the resource utilization of steel slag and improving the clinker performance.

[0037] Clinker often contains no or very small amounts of zinc, copper, manganese or lithium, and tricalcium silicate is mainly monoclinic M3 crystal type. The present invention introduces a quenching and tempering material into the clinker, which not only realizes steel slag as a raw material for producing cement clinker, but also introduces a certain amount of zinc, copper, manganese or lithium into the clinker, and can prepare low-carbon high-performance cement clinker containing highly active R-type tricalcium silicate.

[0038] The steel slag in the present invention includes CaO, SiO2, A12O3, MgO and Fe2O3, etc.

[0039] Embodiment 1: The designed usage of tempering material, steel slag and raw meal are 5%, 20% and 75% respectively. The clinker rate values ​​are KH=0.898, SM=2.50, IM=1.31 respectively, and the tempering material is prepared from copper slag. Tempering material is not used in the clinker of comparative example 1. The calculated chemical composition of the clinker is shown in Table 2. The tempering material, steel slag and raw meal are matched and mixed evenly according to the calculated composition, and after mixing, they are calcined in a high-temperature furnace at 1430℃ and then rapidly cooled. The cooled clinker is crushed and ground to control the specific surface area of ​​the clinker to (340±20) m 2 / kg.

[0040] Table 2 Chemical composition of clinker (wt%) <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[SO3]]> <![CDATA[K2O]]> <![CDATA[Na2O]]> CuO Comparative Example 1 21.29 4.83 3.68 62.99 6.30 0.30 0.31 0.31 0 Example 1 21.16 4.80 3.66 62.61 6.26 0.29 0.31 0.31 0.60 The clinker samples were tested by XRD diffraction, and the X-ray diffraction peaks of the clinker in the characteristic fingerprint area of ​​31°~33° and 51°~53° were given. Figure 1 As shown, in Comparative Example 1, no quenching and tempering material is used in the clinker, but due to the solid solution of other impurities, the diffraction spectrum between 31° and 33° The interplanar spacing of (224) is close, and the diffraction peaks of the two crystal planes merge; there is a shoulder peak on the right side of the (620) diffraction peak between 51° and 53°, which is the (040) diffraction peak of the monoclinic M3 crystal form. Therefore, the tricalcium silicate in the clinker of Comparative Example 1 is the M3 crystal form. Figure 2 As shown, since the clinker in Example 1 uses a tempering material, the diffraction spectrum has only two diffraction peaks at 32°~33°, and only one R-type (220) crystal plane diffraction peak between 51°~53°, indicating that the tricalcium silicate in the clinker in Example 1 is R-type.

[0041] The clinker prepared above was mixed with 5% gypsum, and the compressive strength test of the clinker sample was carried out according to GB / T17671-1999. The water-cement ratio was 0.5, and water was added to mix to make a 40mm×40mm×40mm mortar test block. According to the standard curing, the compressive strength of the 3-day, 7-day, 28-day and 90-day blocks was measured, as shown in Table 3.

[0042] Table 3 Free calcium content, specific surface area and strength properties of clinker samples Embodiment 2: The designed usage of tempering material, steel slag and raw meal are 6%, 14% and 80% respectively. The clinker rate values ​​are KH=0.902, SM=2.45, IM=1.35 respectively, and the tempering material is prepared from lead-zinc slag. Tempering material is not used in the clinker of Comparative Example 2. The calculated chemical composition of the clinker is shown in Table 4. The tempering material, steel slag and raw meal are matched and mixed evenly according to the calculated composition, and after mixing, they are calcined in a high-temperature furnace at 1450℃ and then rapidly cooled. The cooled clinker is crushed and ground to control the specific surface area of ​​the clinker to (340±20) m 2 / kg.

[0043] Table 4 Chemical composition of clinker (wt%) <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[SO3]]> <![CDATA[K2O]]> <![CDATA[Na2O]]> ZnO Comparative Example 2 21.13 4.96 3.67 63.03 6.29 0.30 0.31 0.31 0 Example 2 20.07 4.72 3.49 59.89 5.97 0.28 0.29 0.30 5.00 The clinker samples were tested by XRD diffraction. The tricalcium silicate in the clinker of Comparative Example 2 was of M3 crystal type, and the tricalcium silicate in the clinker of Example 2 was of R crystal type.

[0044] The clinker prepared above was mixed with 5% gypsum, and the compressive strength test of the clinker sample was carried out according to GB / T17671-1999. The water-cement ratio was 0.5, and water was added to mix to make a 40mm×40mm×40mm mortar test block. According to the standard curing, the compressive strength of the 3-day, 7-day, 28-day and 90-day blocks was measured, as shown in Table 5.

[0045] Table 5 Free calcium content, specific surface area and strength properties of clinker samples Embodiment 3: The designed usage of tempering material, steel slag and raw meal are 4%, 6% and 90% respectively, and the tempering material contains phosphorus. The designed clinker rate values ​​are KH=0.892, SM=2.40, IM=1.42 respectively, and the tempering material is prepared from manganese slag. Tempering material is not used in the clinker of comparative example 3. The calculated chemical composition of the clinker is shown in Table 6. The tempering material, steel slag and raw meal are matched and mixed evenly according to the calculated composition, and after mixing, they are calcined in a high-temperature furnace at 1410℃ and then rapidly cooled. The cooled clinker is crushed and ground to control the specific surface area of ​​the clinker to (340±20) m 2 / kg.

[0046] Table 6 Chemical composition of clinker (wt%) <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO <![CDATA[SO3]]> <![CDATA[K2O]]> <![CDATA[Na2O]]> <![CDATA[MnO2]]> Comparative Example 3 21.16 5.17 3.64 62.88 6.24 0.29 0.31 0.31 0 Example 3 21.07 5.15 3.63 62.60 6.21 0.29 0.30 0.31 4.5 The clinker samples were tested by XRD diffraction. The tricalcium silicate in the clinker of Comparative Example 3 was of M3 crystal type, and the tricalcium silicate in the clinker of Example 3 was of R crystal type.

[0047] The clinker prepared above was mixed with 5% gypsum, and the compressive strength test of the clinker sample was carried out according to GB / T17671-1999. The water-cement ratio was 0.5, and water was added to mix to make a 40mm×40mm×40mm mortar test block. According to the standard curing, the compressive strength of the 3-day, 7-day, 28-day and 90-day blocks was measured, as shown in Table 7.

[0048] Table 7 Free calcium content, specific surface area and strength properties of clinker samples The above embodiments are only exemplary embodiments of the present invention and are not intended to limit the present invention. The protection scope of the present invention is defined by the claims. Those skilled in the art may make various modifications or equivalent substitutions to the present invention within the essence and protection scope of the present invention, and such modifications or equivalent substitutions shall also be deemed to fall within the protection scope of the present invention.

Claims

1. A low-carbon high-performance cement clinker, characterized in that: The raw materials in the cement clinker include the following components by weight percentage: 75-90% raw material, 5-20% steel slag and 2-8% quenching and tempering material. The tempering material includes at least two of lead-zinc slag, copper slag, manganese slag and lithium slag.

2. A low-carbon high-performance cement clinker according to claim 1, characterized in that: The lead-zinc slag in the tempering material has a weight percentage of 0-5.5% as ZnO oxide; the copper slag has a weight percentage of 0-2.0% as CuO oxide; the manganese slag has a weight percentage of 0-7.0% as MnO2 oxide; and the lithium slag has a weight percentage of 0-3.0wt% as Li2O oxide.

3. A low-carbon high-performance cement clinker according to claim 1, characterized in that: The minerals in the cement clinker include tricalcium silicate in a content of 45-70wt% by weight, and its crystal form is R type.

4. The low-carbon high-performance cement clinker according to claim 1, characterized in that: The limestone saturation coefficient of the cement clinker is in the range of 0.82-0.94%; the silicon content is in the range of 1.7-2.7%; and the aluminum content is in the range of 0.8-1.7%.

5. The low-carbon high-performance cement clinker according to claim 1, characterized in that: The steel slag is not ground, and the particle size of the steel slag is ≤15mm.

6. A method for preparing the low-carbon high-performance cement clinker according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1, selecting the type of conditioning material according to the required composition of cement clinker, and determining the weight ratio of each conditioning material component; Step 2: fully mix the raw meal, steel slag and the above-mentioned tempering material, then calcine at high temperature and quickly cool to room temperature to prepare cement clinker.

7. The method for preparing low-carbon high-performance cement clinker according to claim 6, characterized in that: The temperature range of high temperature calcination is 1400℃~1500℃.

8. The method for preparing low-carbon high-performance cement clinker according to claim 6, characterized in that: Grind the obtained cement clinker to control the sample fineness and grind it to a specific surface area of ​​320~360m 2 / kg.

Citation Information

Patent Citations

  • Portland cement clinker and preparation method thereof

    CN104058617A

  • Steel slag cement

    CN104556753A

  • Cement clinker and preparation method and application thereof

    CN106698982A

  • High strength silicate clinker and its preparing method

    CN1587157A

Cited By

  • Method for preparing high-sulfur iron aluminate cement by using steel slag iron extraction tailings

    CN122010431A

  • Method for preparing high-sulfur ferroaluminate cement using iron extraction tailings from steel slag

    CN122010431B